Moderating Effect of Government Policies on the Relationship between Corporate Social Responsibility Initiatives and Financial Performance of Cement Manufacturing Companies in Kenya - Mbole, Uvyu C.; Arasa, Robert; Mang’unyi, E. Eric (Journal of African Interdisciplinary Studies (JAIS), 2021)
The purpose of this study was to determine the moderating effect of government policies (GP) on the relationship between Corporate Social Responsibility (CSR) and Financial Performance (FP) of cement manufacturing companies in Kenya. The study undertook an extensive literature review that looked into the history of CSR, CSR theories, different CSR models and an empirical review on the topic. The study adopted a positivism research paradigm approach. The survey design collected both primary and secondary data. The data was analyzed using both descriptive and inferential statistics. The relationship of interest was established using Structural Equation Modelling (SEM). The study population comprised of workers in cement manufacturing companies in Kenya. The total population was 624 and sample size was 255. A response rate of 80.3% was achieved. The study established that government policies have a negative moderating effect (beta=-0.891) on the relationship between corporate social responsibility initiatives and financial performance of cement manufacturing companies in Kenya. The study concluded that GP has a negative effect on the relationship between CSR initiatives and FP. Based on the research findings, the study recommends that cement manufacturing companies should endear to understand different government policies that have implications on the relationships between corporate social responsibility and financial performance and align their operations accordingly. The study suggests that further research should be undertaken to look into government policies that promotes corporate social responsibilities towards providing a win-win situation for the government, corporates and any other stakeholder affected by any form of corporate social responsibility engagement.
Keywords: Corporate Social Responsibility; Financial Performance; Government Policies; Cement manufacturing firms